Associations between socioeconomic position and correlates of sedentary behaviour among youth: a systematic review. Issue 11 (28th August 2015) - Gebremariam, M. K.; Altenburg, T. M.; Lakerveld, J.; Andersen, L. F.; Stronks, K.; Chinapaw, M. J.; Lien, N.
Summary Existing research evidence indicates that children and adolescents of parents with a low socioeconomic position spend more time on sedentary behaviour than their counterparts. However, the mechanisms driving these differences remain poorly understood. The main aim of this systematic review was to summarize the evidence regarding the association between socioeconomic position and correlates of sedentary behaviour among youth (0–18 years) from developed countries. The literature search was conducted using MEDLINE, Embase, CINAHL and PsycINFO. A total of 37 studies were included. All but three studies examined screen‐based sedentary behaviours only. Methodological quality ranged from low to moderate. Education was the most commonly used indicator of socioeconomic position, followed by income. Socioeconomic position was inversely related to the presence of a TV in the child's bedroom, parental modelling for TV viewing, parental co‐viewing and eating meals in front of the TV. We found no/indeterminate evidence for an association between socioeconomic position and rules and regulations about screen time. The findings suggest possible factors that could be targeted in future intervention studies to decrease screen‐based sedentary behaviour in lower socioeconomic groups in particular.